Matrimonio e famiglia tra laicità e libertà religiosa (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Premessa: la necessaria precedenza della libertà religiosa sulla laicità - 2. Radici etico-religiose del matrimonio, libertà religiosa e origini del matrimonio civile - 3. Il matrimonio civile: tra neutralità e ideologia - 4. Ritorno del fenomeno religioso nell’età della secolarizzazione: ricadute in materia matrimoniale - 5. La restituzione di matrimonio e famiglia alla società civile e alla religione - 6. La (ri)conquista di spazi di “diritto personale” e ritorno alla disciplina religiosa del matrimonio - 7. Diritto alla tutela dell’identità e “princìpi non negoziabili” dello Stato democratico. Conclusioni.Marriage and family between secularism and religious freedomAbstract: Given that between secularism and religious freedom there is a relationship of instrumentality of the first compared to the second, in the essay there’s a recall to the ethical-religious roots of the marriage’s legislation, which, starting from the Protestant Reformation and then from the French Revolution has undergone a process of secularization and secularism with the birth of the civil marriage. It is a process that has been motivated (also) by reasons of religious freedom, but which has led, by the State, to the subtraction of the marriage’s subject from the society. Today there is a substantial return from the state to the society of the discipline about the various forms of life and family communions, and this, in a religiously pluralistic society, involves (also) the return of the marriage to the religion.